Lippincott's intrapartum emergencies - Lippincott Williams & Wilkins (Philadelphia : Lippincott Williams & Wilkins, 1999)
This interactive CD-ROM offers hands-on experience in assessing and intervening during intrapartum emergencies. Four separate case studies simulate the labor and delivery experiences of clients in emergency situations.
System requirements : 486 66mhz or faster CPU Window 3.1 or highher 76 MB hard drive space free 16MB RAM 640x480 monitor, 256 colors CD-ROM drive Sound card
Keywords: Delivery -- methods; Pregnancy, High-Risk